MAPING AND DETECTING FALLOWED AREA OF CULTIVATED TIGER SHRIMP PONDS OF COASTAL PROVINCES BY USING REMOTE SENSING DATA - Thao, Nguyen Van; Cu, Nguyen Duc; Thanh, Nguyen Xuan (Vietnam Journal of Marine Science and Technology, 2012)
In recent years yield of srhrimp culture in Viet Nam has decreased due to epidemic diseases and pollution. Brackish waters ponds built for shrimp culture have been changed for fish and crab culture with low economic benefits or falloved. Identification of fallwed area of srhimp ponds is significant to policy makers in managing coastal resources. The research using remote sensing indicates that the fallowed area of srhimp culture ponds in 2008 are 28821ha in north and north central; 13907ha in central and 67.591 in south region, indicating the total of 110320ha for the entire country. It is noted that the fallowed area reported by provincial authority in 2008 is around 78590ha which is less much (31730ha or 40%) in comparision with this research.